Labor Force Analysis in Food and Beverage Establishments in Kyrgyzstan: A Descriptive Study - Erdem, Barış; Samatova, Gülmira; Turganbayeva, Nadira; Turdubekova, Sapargül; İsakova, Dinara (Turizam, 2019)
In this research were aimed to determine the profiles of employees working at food and beverage establishments in Kyrgyzstan. Data of the research are collected by survey technique from 304 employees who work in different positions of 39 food and beverage establishments in Bishkek. According to findings; more than half of the employees are female and single, a majority of them are between 17 and 30 years old and more than 50% of the participants are vocational school or bachelor graduates. In addition to these findings, the results indicate that around one of every two participants have no tourism education at any level. It is revealed that almost half of the participants work from 9 to 12 hours and average wage of most of these employees is under 250 dollars per month. Nevertheless, it was detected that almost half of the participants were generally pleased to work in food and beverage sector. Keywords: Food and Beverage Establishments, Human Resources, Kyrgyzstan.